A novel dual DYRK1A/B inhibitor for the treatment of type 1 diabetes - Tumas, Šarūnas; Mingaila, Jonas; Baranauskas, Vytautas; Baltrukonytė, Emilija; Orla, Laurynas; Krasko, Jan Aleksander; Pocevičiūtė, Roberta; Berlina, Dina; Belenky, Alexei; Vilenchik, Maria; Vaitkevičienė, Agnė; Potapova, Olga; et al. (Frontiers in Pharmacology, 2025)
BackgroundType 1 diabetes (T1D) is an autoimmune disease that leads to the progressive destruction of pancreatic β cells, resulting in insulin deficiency and hyperglycemia. Current treatments focus on insulin replacement, but novel therapeutic approaches targeting β cell regeneration are needed. Dual-specificity tyrosine-phosphorylation-regulated kinases 1A (DYRK1A) and 1B (DYRK1B) play key roles in cell cycle regulation and β cell proliferation.MethodsIn this study, FX8474, a novel DYRK1 inhibitor, was evaluated in a streptozotocin (STZ)-induced diabetic mouse model. Mice were treated orally for 7 days, and pharmacokinetics, glucose regulation, and immune cell profiling were assessed.ResultsPharmacokinetic analysis confirmed the oral bioavailability of FX8474, and treatment was associated with improved fasted glucose levels and glucose tolerance after a 7-day treatment. Immunophenotyping indicated that FX8474 treatment increases CD4+ memory T cell populations while decreasing CD4+ effector cells, as well as restores CD8+ T cell phenotypes to levels observed in healthy mice.ConclusionFX8474 has a modest effect on glucose regulation and immune cell composition, warranting further investigation into its potential therapeutic applications.